2020
DOI: 10.26633/rpsp.2020.56
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring inequality changes in full immunization coverage in infants in Latin America and the Caribbean

Abstract: Objective. To compare inequalities in full infant vaccination coverage at two different time points between 1992 and 2016 in Latin American and Caribbean countries. Methods. Analysis is based on recent available data from Demographic and Health Surveys, Multiple Indicator Cluster Surveys, and Reproductive Health Surveys conducted in 18 countries between 1992 and 2016. Full immunization data from children 12–23 months of age were disaggregated by wealth quintile. Absolute and relative inequalities between the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 13 publications
0
14
0
2
Order By: Relevance
“…Past research suggests that compounding factors, including large subnational disparities in access to vaccines and shifting perceptions of vaccine risk, could have contributed to regional declines. 35 , 36 , 37 By 2019, only 109 of 204 countries and territories reached at least 90% mean estimated coverage for DTP3, while only 11 countries and territories met this threshold across nine of the assessed vaccines.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Past research suggests that compounding factors, including large subnational disparities in access to vaccines and shifting perceptions of vaccine risk, could have contributed to regional declines. 35 , 36 , 37 By 2019, only 109 of 204 countries and territories reached at least 90% mean estimated coverage for DTP3, while only 11 countries and territories met this threshold across nine of the assessed vaccines.…”
Section: Discussionmentioning
confidence: 97%
“…Past research suggests that compounding factors, including large subnational disparities in access to vaccines and shifting perceptions of vaccine risk, could have contributed to regional declines. [35][36][37] By 2019, only 109 of 204 countries and territories reached at least 90% mean estimated coverage for DTP3, while only 11 countries and territories met this threshold across nine of the assessed vaccines. Improving and sustaining advances in vaccination requires a constellation of local and global factors, and our analysis further emphasises that progress in routine immunisation is far from inevitable.…”
Section: Global Gains and Challenges In Routine Immunisationmentioning
confidence: 99%
“… 26 As such, efforts are needed to guarantee continuity in vaccine uptake, given that lockdown and isolation measures have negatively impacted national coverage during 2020, especially among rural populations. Although there have been successful efforts to reduce rural/urban inequalities, 6 new vaccination agendas (including those proposed for COVID-19 containment) must include special actions to overcome lags in routine childhood immunisation for at-risk regions.…”
Section: Discussionmentioning
confidence: 99%
“… 3 For low-income and middle-income countries, the effects of these disruption may be even more detrimental to achieving optimal immunisation coverage for poor households and remote or rural areas. 4 5 Although inequities are decreasing in Latin America, 6 infectious outbreaks such as COVID-19 have the potential to affect what has been achieved by diverting health resources from preventive healthcare and through lockdown measures that contribute to reducing normal delivery of vaccines, especially in remote areas.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have identified negative changes in comprehensive vaccination coverage over time among infants from disadvantaged households. 27 Taking into account the decrease in subnational coverage of Penta3 below the threshold recommended by the WHO, the increase in the number of partially and unvaccinated infants and the appearance of sporadic cases of diphtheria, tetanus and pertussis, there is a significant risk of outbreaks of immunopreventable diseases in these provinces that could be exacerbated by the current pandemic. 8,28 Compared to 2019 and until March 2021, the incidence rate of diphtheria (0.38), tetanus (0.34) and pertussis (0.19) per 100,000 inhabitants increased 383%, 45% and 21%, respectively.…”
Section: Discussionmentioning
confidence: 99%